Gender dimorphic increase in RBP‐4 and NGAL in children born after IVF: an epigenetic phenomenon?. (15th March 2013) - Sakka, Sophia D.; Margeli, Alexandra; Loutradis, Dimitrios; Chrousos, George P.; Papassotiriou, Ioannis; Kanaka‐Gantenbein, Christina
Abstract Background In vitro fertilisation (IVF) has been widely used during the last decades. Recent studies demonstrated some alterations in IVF children's metabolic profile compared with controls. The recently reported lipocalins retinol‐binding protein 4 (RBP‐4) and neutrophil gelatinase‐associated lipocalin (NGAL), as well as visfatin, which are associated with glucose intolerance and could help in the early detection of metabolic abnormalities, have not been studied in IVF children as yet. We studied the lipocalins RBP‐4 and NGAL as well as visfatin in children born after IVF. Subjects and methods A total of 100 children born after IVF (47 boys) and 60 controls born after normal conception (30 boys), aged 4–14 year, were studied cross‐sectionally. All children had a physical examination, their fasting glucose, insulin, lipid profile, RBP‐4, NGAL, and visfatin were determined and their homoeostasis model assessment (HOMA) index was calculated. Results Children born after IVF had significantly higher RBP‐4 (P = 0·009) and NGAL (P = 0·028) levels than controls. When divided by gender, RBP‐4 remained higher in IVF girls (P = 0·002), whereas NGAL was higher in IVF boys (P = 0·021). Linear regression analysis had revealed that the differences are attributed to the IVF procedure per se. Conclusions In our study, IVF children had significantly higher RBP‐4 and NGAL levels than controls, suggesting early metabolic derangements that could be attributed to an epigenetic phenomenon. These results are in accordance with our earlier findings of higher blood pressure and triglycerides in IVF children than controls. Further prospective studies in IVF children will determine the natural course of their metabolic profile.